Pemisahan squalene dan fatty acid sterol esters dari soybean oil deodorizer distillate - Setiyo Gunawan; Yi Hsu Ju (ASOSIASI PENDIDIKAN TINGGI TEKNIK KIMIA INDONESIA (APTEKIM), 2008)
Depending on conditions in the refining process, soybean oil deodorizer distillate (SODD) contains 42-51% free fatty acids (FFA) and 16-25% triacylglycerol (TAG). Bioactive compounds such as tocopherols, free phytosterols, fatty acid steryl esters (FASE) and squalene also make up a significant portion of SODD. The efficient removal of FFA and TAG is a crucial step in the isolation and purification of bioactive compounds from SODD. In this work, a modified soxhlet extraction technique was developed and its optimal operation conditions were determined for the efficient removal of FFA and TAG from SODD. Starting with SODD that contains 3.53% FASE and 1.99% squalene, it was possible to obtain a fraction enriched with FASE (22.0%, recovery 91.3%) and squalene (8.63%, recovery 100%) by this modified soxhlet extraction under the following operation conditions: SODD/(silica gel) = 1/3 (w/w), extraction temperature = -6°C, number of extraction/h = 8.7. FFA remained in this FASE and squalene enriched fraction is 38.7% and there was no detectable TAG. The percentage removal of FFA and TAG for this FASE and squalene enriched fraction are 84.29% and 100%, respectively. The advantages of modified soxhlet extraction over open-column chromatography are that less solvent usage, larger sample size per batch and shorter operation time.Keywords: Fatty acid steryl ester; free fatty acid; modified soxhlet extraction; soybean oil deodorizer distillate; squalene; triacylglycerol AbstrakDalam proses pemurnian minyak kedelai, produk samping dari proses penghilangan bau (soybean oil deodorizer distillate, SODD) mengandung 42-52% free fatty acids (FFA) dan 18-28% triacylglycerols (TAG). Komponen bioaktif seperti tocopherols, free phytosterols, fatty acid steryl esters (FASE) dan squalene juga mempunyai kontribusi yang besar dalam komposisi SODD. Efisiensi penghilangan FFA dan TAG adalah langkah yang sangat penting dalam pemisahan dan pemurnian komponen bioaktif dari SODD. Dalam penelitian ini, modifikasi soxhlet ekstraksi telah ditemukan dan optimisasi kondisi operasi ditentukan berdasarkan efisiensi penghilangan FFA dan TAG dari SODD. Fraksi lemak non polar (nonpolar lipid fraction, NPLF) dengan kandungan FASE (22.0%, recovery 91.3%) dan squalene (8.63%, recovery 100%) telah diperoleh dengan menggunakan modifikasi soxhlet ektraksi dengan kondisi operasi: SODD/(silica gel) = 1/3 (w/w), dan suhu ekstraksi = -6°C. FFA dan TAG yang tersisa di NPLF secara berurutan adalah 38.7% dan 0%. Persentase penghilangan FFA dan TAG di NPLF secara berurutan adalah 84.29% and 100%. Keuntungan menggunakan modifikasi soxhlet ekstraksi dibandingkan dengan silica gel column chromatography adalah sedikitnya pelarut yang digunakan, besarnya sampel per unit batch yang digunakan, dan pendeknya waktu operasi.Kata kunci: Free fatty acid, fatty acid steryl ester, modifikasi soxhlet ekstraksi, soybean oil deodorizer distillate, squalene, triacylglycerols